2018
DOI: 10.1186/s12889-018-5472-z
|View full text |Cite
|
Sign up to set email alerts
|

Physical inactivity, gender and culture in Arab countries: a systematic assessment of the literature

Abstract: BackgroundPhysical inactivity is associated with excess weight and adverse health outcomes. We synthesize the evidence on physical inactivity and its social determinants in Arab countries, with special attention to gender and cultural context.MethodsWe searched MEDLINE, Popline, and SSCI for articles published between 2000 and 2016, assessing the prevalence of physical inactivity and its social determinants. We also included national survey reports on physical activity, and searched for analyses of the social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
176
2
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 193 publications
(208 citation statements)
references
References 167 publications
19
176
2
11
Order By: Relevance
“…16 However, the majority of children [17][18][19][20][21] and youth [19][20][21][22][23][24][25] do not meet the current recommendations of 60 minutes of MVPA per day 26 in very high HDI European and North American countries and regions. Similar findings were observed among children and/or adolescents from other very high HDI countries or regions such as Australia, 6 Chile, 27 Chinese Taipei (Taiwan), 28 Hong Kong, 29 Japan, 30 South Korea, 31 Qatar, 32 and the United Arab Emirates. [32][33][34] Very high HDI countries share similar characteristics in terms of education, life expectancy, and income; however, differences also exist geographically, politically, culturally, religiously, and environmentally that may influence physical activity behavior differently across the very high HDI countries.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…16 However, the majority of children [17][18][19][20][21] and youth [19][20][21][22][23][24][25] do not meet the current recommendations of 60 minutes of MVPA per day 26 in very high HDI European and North American countries and regions. Similar findings were observed among children and/or adolescents from other very high HDI countries or regions such as Australia, 6 Chile, 27 Chinese Taipei (Taiwan), 28 Hong Kong, 29 Japan, 30 South Korea, 31 Qatar, 32 and the United Arab Emirates. [32][33][34] Very high HDI countries share similar characteristics in terms of education, life expectancy, and income; however, differences also exist geographically, politically, culturally, religiously, and environmentally that may influence physical activity behavior differently across the very high HDI countries.…”
supporting
confidence: 78%
“…Similar findings were observed among children and/or adolescents from other very high HDI countries or regions such as Australia, 6 Chile, 27 Chinese Taipei (Taiwan), 28 Hong Kong, 29 Japan, 30 South Korea, 31 Qatar, 32 and the United Arab Emirates. [32][33][34] Very high HDI countries share similar characteristics in terms of education, life expectancy, and income; however, differences also exist geographically, politically, culturally, religiously, and environmentally that may influence physical activity behavior differently across the very high HDI countries. Cooper et al 35 found that there was substantial between-country variation in objectively measured MVPA in the International Children's Accelerometry Database, even between apparently similar countries, and concluded that further research is needed to explore environmental and sociocultural explanations for these differences.…”
supporting
confidence: 78%
“…This finding of generally high levels of overweight in the MENA region aligns with other evidence from the region highlighting elevated prevalence of obesity in children and women and may be explained by the particularly high penetration of globalized food markets in the MENA region and weaker policies to promote breastfeeding and regulate unhealthy foods, including to infants and children (Abarca‐Gómez et al, ; Akik, Ghattas, Filteau, & Knai, ; Colchero, Rivera‐Dommarco, Popkin, & Ng, ; Fraser, ). Additional cultural factors such as notions of beauty and health and social restrictions on physical activity may contribute to these differences across regions (Obermeyer, Bott, & Sassine, ; Sharara, Akik, Ghattas, & Obermeyer, ). It may be that the co‐occurrence of stunting and overweight, which was reported in LAC populations a decade ago, has stimulated some action at the policy level to reduce both these burdens (Hodge, Verstraeten, & Ochoa‐Avilés, ; Hoey & Pelletier, ; Huicho et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that for these interventions to be more effective, parents and school-teachers need to be more actively engaged and educated. Cultural norms related to girls' participation in PA in general, and as they reach pubescence in particular were not explicitly discussed by our respondents but should be addressed in the future as researchers have reported religious norms shaping girls' access to PA in other Muslim majority societies [17]. And it is imperative that effective interventions be found as, counter to many parents' and educators' beliefs, PA has the potential to improve academic achievement and cognitive development [45,46] and to reduce the risk of children being overweight and obese [32].…”
Section: Plos Onementioning
confidence: 99%
“…The influence of social factors on PA has been described by researchers around the world. A review of literature from Arab countries and among the Indian diaspora living in Canada showed the importance of gender roles, religious identity and cultural norms shaping support for PA for children [16,17]. Researchers have reported that parental support for PA is positively associated with PA among children [12,18].…”
Section: Introductionmentioning
confidence: 99%